The electrophysiology of thyroid surgery: electrophysiologic and muscular responses with stimulation of the vagus nerve, recurrent laryngeal nerve, and external branch of the superior laryngeal nerve. (4th July 2016) - Liddy, Whitney; Barber, Samuel R.; Cinquepalmi, Matteo; Lin, Brian M.; Patricio, Stephanie; Kyriazidis, Natalia; Bellotti, Carlo; Kamani, Dipti; Mahamad, Sadhana; Dralle, Henning; Schneider, Rick; Dionigi, Gianlorenzo; et al.
Abstract : Objectives/Hypothesis: Correlation of physiologically important electromyographic (EMG) waveforms with demonstrable muscle activation is important for the reliable interpretation of evoked waveforms during intraoperative neural monitoring (IONM) of the vagus nerve, recurrent laryngeal nerve (RLN), and external branch of the superior laryngeal nerve (EBSLN) in thyroid surgery. Study Design: Retrospective chart review. Methods: Data were reviewed retrospectively for thyroid surgery patients with laryngeal nerve IONM from January to December, 2015. EMG responses to monopolar stimulation of the vagus/RLN and EBSLN were recorded in bilateral vocalis, cricothyroid (CTM), and strap muscles using endotracheal tube‐based surface and intramuscular hook electrodes, respectively. Target muscles for vagal/RLN and EBSLN stimulation were the ipsilateral vocalis and CTM, respectively. All other recording channels were nontarget muscles. Results: Fifty surgical sides were identified in 37 subjects. All target muscle mean amplitudes were significantly higher than in nontarget muscles. With vagal/RLN stimulation, target ipsilateral vocalis mean amplitude was 1, 095.7 μV (mean difference range = −814.1 to −1, 078 μV, P < .0001). For EBSLN stimulation, target ipsilateral CTM mean amplitude was 6, 379.3 μV (mean difference range = −6, 222.6 to −6, 362.3 μV, P < .0001). Target muscle large‐amplitude EMG responses correlated with meaningful visual or palpable muscular responses, whereas nontarget EMG responses showed no meaningful muscle activation. Conclusions: Target and nontarget laryngeal muscles are differentiated based on divergence of EMG response directly correlating with presence or absence of visual and palpable muscle activation. Low‐amplitude EMG waveforms in nontarget muscles with neural stimulation can be explained by the concept of far‐field artifactual waveforms and do not correspond to a true muscular response. The surgeon should be aware of these nonphysiologic waveforms when interpreting and applying IONM during thyroid surgery. Level of Evidence: 4 Laryngoscope, 127:764–771, 2017